Joint pain in children - A. N. Kozhevnikov; N. A. Pozdeeva; M. A. Konev; M. S. Nikitin; A. I. Bryanskaya; E. V. Prokopovich; K. A. Afonichev; G. A. Novik (Лечащий Врач)
Joint pain in children is a common problem of a growing body. Arthralgia is diagnosed erroneously, sometimes despite the fact that the problem has been studied enough. The purpose of this article is a detailed description of different forms of benign and pathologic arthralgia in children. The article contains modern ideas about the causes of children’s arthralgia and description of the pain as one of the symptoms of various forms of joint disease. The features of clinical and instrumental diagnosis of joint pathology in children are clearly presented.